2006
DOI: 10.1016/j.otohns.2006.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic transeptal surgery for choanal atresia with a stentless folded‐over‐flap technique

Abstract: This technique was satisfactory and safe, allowing fast recovery in a one-step surgery, using neither stents nor nasal packing. Long-term patency with no reduction in functional quality was also observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 19 publications
(34 reference statements)
0
17
0
1
Order By: Relevance
“…Other authors have reported that the management of bony atresia is more challenging than the management of atresia with a membranous component, 3,7 possibly due to neo-osteogenesis as described by Ayari et al 9 We also found that patients with syndromeassociated atresia were more likely to need revision surgery than patients with isolated disease (4 of 10 choanae [40%] vs 5 of 33 choanae [15%], P = .17). Studies 5,[10][11][12] have also found higher rates of restenosis in patients with syndromic CA, although 2 recent studies 3,7 found no significant difference in the 2 groups.…”
Section: Type Of Atresiamentioning
confidence: 99%
“…Other authors have reported that the management of bony atresia is more challenging than the management of atresia with a membranous component, 3,7 possibly due to neo-osteogenesis as described by Ayari et al 9 We also found that patients with syndromeassociated atresia were more likely to need revision surgery than patients with isolated disease (4 of 10 choanae [40%] vs 5 of 33 choanae [15%], P = .17). Studies 5,[10][11][12] have also found higher rates of restenosis in patients with syndromic CA, although 2 recent studies 3,7 found no significant difference in the 2 groups.…”
Section: Type Of Atresiamentioning
confidence: 99%
“…(11) Also, Cedin AC, et al used stentless folded -over-flap technique and no recurrent cases were found. (12) A study done by El-Ahl MA, et al using the same technique showed a zero recurrence rate. (13) Also Magdy ES in his comparative study between stent and non-stent groups found that the use of stents didn't decrease the re-closure or restenosis rate.…”
Section: Discussionmentioning
confidence: 94%
“… Minimized operative trauma with creation of possibly small wound surfaces requiring epithelization so that cutting or punching instruments are appropriate. Creation of opposed mucosal flaps to cover critical wound surfaces [ 640 ], [ 641 ], [ 642 ], [ 643 ], [ 644 ], [ 645 ], [ 646 ]. The application of slightly curved shaver drills for removal of bone in addition to bone punches has to be preferred to the classical drilling system because of a better view and avoidance of an overheated surgical site.…”
Section: Indications Of Surgery Beyond Chronic Rhinosinusitismentioning
confidence: 99%
“…Creation of opposed mucosal flaps to cover critical wound surfaces [ 640 ], [ 641 ], [ 642 ], [ 643 ], [ 644 ], [ 645 ], [ 646 ].…”
Section: Indications Of Surgery Beyond Chronic Rhinosinusitismentioning
confidence: 99%